Hollow organosilica beads as reference particles for optical detection of extracellular vesicles. (15th July 2018) - Varga, Z.; van der Pol, E.; Pálmai, M.; Garcia‐Diez, R.; Gollwitzer, C.; Krumrey, M.; Fraikin, J.‐L.; Gasecka, A.; Hajji, N.; van Leeuwen, T. G.; Nieuwland, R.
Abstract : Essentials Standardization of extracellular vesicle (EV) measurements by flow cytometry needs improvement. Hollow organosilica beads were prepared, characterized, and tested as reference particles. Light scattering properties of hollow beads resemble that of platelet‐derived EVs. Hollow beads are ideal reference particles to standardize scatter flow cytometry research on EVs. Summary: Background: The concentration of extracellular vesicles (EVs) in body fluids is a promising biomarker for disease, and flow cytometry remains the clinically most applicable method to identify the cellular origin of single EVs in suspension. To compare concentration measurements of EVs between flow cytometers, solid polystyrene reference beads and EVs were distributed in the first ISTH‐organized interlaboratory comparison studies. The beads were used to set size gates based on light scatter, and the concentration of EVs was measured within the size gates. However, polystyrene beads lead to false size determination of EVs, owing to the mismatch in refractive index between beads and EVs. Moreover, polystyrene beads gate different EV sizes on different flow cytometers. Objective: To prepare, characterize and test hollow organosilica beads (HOBs) as reference beads to set EV size gates in flow cytometry investigations. Methods: HOBs were prepared with a hard template sol‐gel method, and extensively characterized for morphology, size, and colloidal stability. The applicability of HOBs as reference particles was investigated by flow cytometry with HOBs and platelet‐derived EVs. Results: HOBs proved to be monodisperse with a homogeneous shell thickness. Two‐angle light‐scattering measurements by flow cytometry confirmed that HOBs have light‐scattering properties similar to those of platelet‐derived EVs. Conclusions: Because the structure and light‐scattering properties HOBs resemble those of EVs, HOBs with a given size will gate EVs of the same size. Therefore, HOBs are ideal reference beads with which to standardize optical measurements of the EV concentration within a predefined size range.